Comparison of Transfer Pricing methods and their application in disputed tax cases in Indonesian courts - Besdy, Besdy; Pony, Pony; Abraham, Abraham; Sitompul, Ariman (Universitas Dharmawangsa, 2024)
Transfer pricing is a trending topic of taxation in various worlds, not least in Indonesia. Directorate General of Taxation is very aggressive to supervise and monitor the practices of transfer pricing conducted by the taxpayer, because it is not just a case of fictitious tax refunds and tax realtor practices that erode the potential for state revenue from taxes, but the practice of tax evasion in the process transfer pricing is also considered a lot of harm to tax revenue. Transfer pricing practice is actually a common practice and commonly practiced by companies group companies. However, this can be a crucial issue when setting transfer prices is not in accordance with the principle of fairness and business prevalence (PKKU / arm's length principle) which regulated in the Indonesian transfer pricing regulations.. The taxpayer is given the freedom to use their own discretion in deciding the most appropriate method of measuring the transfer price. However, this leads to inconsistencies in the methods applied to arm's length transactions similar by entities from similar industries. Loopholes in this area are vulnerable to tax evasion practices since decades ago. This paper aims to compare the available methods for measurement transfer pricing.